Pentahelix Collaboration as An Attempt to Optimize Sustainable Waste Management Services in Banyumas Regency - Salwa Fitriana; Muhammad Fadil; Arimbi Puspa Karina (Spirit Publik: Jurnal Administrasi Publik, 2025)
The Zero Waste policy in Banyumas Regency has been implemented through the development of an innovative program called Sumpah Beruang (Sulap Sampah Berubah Menjadi Uang), which utilizes digital technology, such as the Salinmas (Sampah Online Banyumas) and Jeknyong (Ojeke Inyong) applications. Through this program, Banyumas Regency has won an award as the best waste management region in Indonesia. However, the effectiveness of the program has declined each year, as indicated by a decrease in the number of application users, while the volume of waste continues to increase. This study aims to identify the factors that influence the success and failure of the sustainability of an effective digital waste management system. This study uses a descriptive qualitative method with a literature review approach. The data obtained was analyzed using the Collaborative Governance theory by Ansell and Gash (2008) with a pentahelix collaboration model involving the government, academics, the community, the media, and the private sector. This approach is aimed at realizing a circular economy that supports the achievement of the Sustainable Development Goals (SDGs), particularly goal 12 on responsible consumption and production. The main idea of the research emphasizes the importance of inclusive and collaborative governance to optimize the performance of the Salinmas and Jeknyong applications, while strengthening the role of stakeholders and the community in reducing waste generation. The results of the study show that the decline in the effectiveness of the Salinmas and Jeknyong applications is due to two main factors, namely the lack of collaboration between stakeholders in system maintenance and the low level of community participation in waste sorting. In addition, to encourage the sustainability of the Salinmas and Jeknyong programs, there is a need to increase collaboration between stakeholders and active community participation so that waste management in Banyumas Regency can be carried out effectively and sustainably.